INFORMATIZATION THOUGHTS WRITTEN COHERENT SPEECH OF PUPILS: DIACHRONY ASPECT - Yurtaev, Dr. Sc. Sergey V.; Izmailowa, Ph.D. Raniya G.; Sheynowa, Ph. D. Tatyana G. (Revista Inclusiones, 2021)
The relevance of the presented research is determined by the value of written coherent speech for the decision of communicative tasks in society, the place that this speech occupies in school education, the influence of the study of speech capabilities of students to make managerial educational decisions. The purpose of this study is to characterize the subject content of written statements connected pupils eleven to fifteen years. The main approach to achieving this goal is a comparative analysis of one-dimensional works of the same students studying in the fifth-ninth grades of Russian-speaking schools. The article presents data on the number of the topics in the writings of students, reflected in their plan works, and no such expression, but represented by students in the text of the essay. The materials of the article are recommended to all those who are engaged in the management of school education.